Nation of outlaws, state of violence : nationalism, Grassfields tradition, and state building in Cameroon - Terretta, Meredith (New African histories series., 2014)
Nation of Outlaws, State of Violence is the first extensive history of Cameroonian nationalism to consider the global and local influences that shaped the movement within the French and British Cameroons and beyond. Drawing on the archives of the United Nations, France, Great Britain, Ghana, and Cameroon, as well as oral sources, Nation of Outlaws, State of Violence chronicles the spread of the Union des populations du Cameroun (UPC) nationalist movement from the late 1940s into the first postcolonial decade. It shows how, in the French and British Cameroon territories administered as UN Trusteeships after the Second World War, notions of international human rights, the promise of Third World independence, Pan-African federation, and national citizenship blended with local political and spiritual practices that resurfaced as the period of European rule came to a close. After French and British administrators banned the party in the mid-1950s, UPC nationalists adopted violence as a revolutionary strategy. In the 1960s, the nationalist vision disintegrated. The postcolonial regime labeled UPC nationalists "outlaws" and rounded them up for imprisonment or execution as the state shifted to single-party rule in 1966. Nation of Outlaws, State of Violence traces the connection between local and transregional politics in the age of Africa's decolonization and the early decades of the Cold War. Rather than stop at official independence as most conventional histories of African nationalist movements do, this book considers postindependence events as crucial to the history of Cameroonian nationalism and to an understanding of the postcolonial government that came to power on 1 January 1960. While the history of the UPC is a story that ends with the party's failure to gain access to political power with independence, it is also a story of the postcolonial state's failure to become a nation.--